Transcriptional and epigenetic control of human naïve CD8+ T cell activation - Hu, Yaqiu; Du, Yuxia; Chen, Xuenuo; Li, Yongguo; Yang, Cheng (Frontiers in Immunology, 2026)
BackgroundThe differentiation of naïve CD8+ T cells into effector cells upon activation is essential for eliminating intracellular pathogens and cancerous cells, although the underlying epigenetic mechanisms remain incompletely characterized.MethodsPeripheral blood mononuclear cells (PBMCs) were obtained from healthy donors. naïve CD8+ T cells were purified and activated with α-CD3/CD28-conjugated microbeads for 0, 24, or 72 h in vitro. Flow cytometry was used to assess cytokine production and activation markers at each time point. Assay for transposase-accessible chromatin using sequencing (ATAC-seq) was performed to identify differentially accessible chromatin regions (DARs). RNA sequencing (RNA-seq) was performed to measure gene expression. Data from ATAC-seq and RNA-seq were integrated to examine the relationship between chromatin accessibility and gene expression. Enriched pathways for DARs and differentially expressed genes (DEGs) were determined by KEGG pathway and gene ontology (GO) enrichment analysis, and transcription factor (TF) binding patterns around these genes were visualized by footprint analysis.ResultsUpon activation, naïve CD8+ T cells showed increased production of IFN-γ, TNF, and IL-2, and elevated expression of CD69 and CD95. Integrated ATAC-seq and RNA-seq analysis identified 568 and 541 dual-upregulated genes (showing both increased chromatin accessibility and expression) at 24 and 72 h post-activation, respectively. These early-response genes were enriched in pathways including pyruvate metabolism and the DNA damage response. Footprint analysis predicted the ETS and bZIP TF families as key regulators driving this coordinated chromatin and transcriptional reprogramming. Furthermore, distinct chromatin remodeling patterns were observed in gene sets associated with memory, effector function, exhaustion, and metabolism, revealing that accessibility changes did not always directly correlate with transcriptional outcomes.ConclusionThis study defines a core set of genes and TFs that critically regulate the initial activation of human naïve CD8+ T cells. These results provide a molecular roadmap for future efforts to engineer more potent and durable CD8+ T cell responses for adoptive cell therapy.